The Influence of Brand Storytelling on Brand Advocacy in Beauty Products: The Mediating Effect of Emotional Attachment - Fitriani Tobing; Muhammad Dharma Tuah Putra Nasution; Syafrida Hafni Sahir; Yossie Rossanty (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
In the competitive digital market, brands must foster emotional attachment with consumers through storytelling that conveys their identity and values. This paper aims to examine the influence of brand storytelling on brand advocacy with emotional brand attachment as a mediating variable in the context of the digital beauty industry in Indonesia. The design of this research is quantitative with a descriptive-causal approach, using data from 200 active consumers of local cosmetic brands collected through an online survey. The analysis technique used is Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The research results show that brand storytelling has a significant positive effect on emotional brand attachment, and this attachment partially mediates the relationship between brand narrative and advocacy behavior. These findings provide a theoretical contribution by confirming the role of affective mechanisms in shaping loyalty and voluntary support among digital consumers, particularly in the context of emerging market countries. From a practical standpoint, these results recommend that marketers prioritize the development of authentic and emotionally resonant storytelling as a strategy to build psychological closeness and encourage consumers to become active advocates for the brand.